Determinación actual y futura de áreas vulnerables a la presencia de Mildiú (Peronospora farinosa) de la Quinua en las zonas productoras de Cotopaxi, 2017 - Asipuela Haro, Eva Cecilia (2017)
In the following resume the vulnerable areas within Peronospora farinose (main source of Mildiu) have been tested in the rural sectors of the parishes of Cotopaxi. The main objectives of this study were to: Identify the vulnerable areas within the presence of Mildiu, to mold a contemporary potential distribution and the future of Mildiu in the province of Cotopaxi with MaxEnt Software and to determine the vulnerable areas in relation to the models of distribution. The method of distribution modeling that was used was the Maximum Entropy (MaxEnt) 3.2.0 based on the presence of 23 registers within the field with bioclimatic variables; it was accomplished by using potential models of current distribution with bioclimatic variables corrected by the ministry of environment of Ecuador and in order to accomplish future prospects bioclimatic variables were used into two time outlooks (the years 2050 and 2080) using the general model of circulation cccma_cgcm3.1, in the settings A2 and B1; it was possible to identify that vulnerable areas within the presence of Peronospora farinosa are located in certain rural areas within parishes of Eloy Alfaro, Cochapamba, Mulalo ,Aláquez, La Victoria, Pilaló, La Esperanza, Cusubamba and Panzaleo. Current and post models of distribution were obtained with a rating of appropriate reliability of AUC 0.958-0946 and finally the models of distribution could be determined where the variables with greater influence for the development of the disease were: annual temperature fluctuation and annual precipitation, presenting a greater potential for distribution of suitability of Mildiu within the area of the studies made. This model offers a great farming opportunity, due to the fact that it allows to identify vulnerable areas and to predict the future of the main disease of the cultivation of quinoa and by this way being able to prevent it and give it an excellent technical management. Key words: Vulnerable areas, potential distribution, Peronospora farinosa, MaxEnt, downsizing and general models of circulation.